Recent advances in clathrin-independent endocytosis - Hemalatha, Anupama (F1000Res, 2019)
Endocytic pathways are broadly classified into clathrin dependent and independent on the basis of the requirement for the coat protein, clathrin. The molecular pathways and mechanisms underlying the formation of clathrin-independent pathways are still being explored, and this review summarizes recent advances and emerging functional roles of these diverse pathways. In particular, this review will discuss the growing consensus on the role of BAR domain proteins and the actin machinery in different clathrin-independent pathways and its significance to the functions fulfilled by these endocytic pathways.